The prevalence and incidence of community-acquired pressure injury: A protocol for systematic review and meta-analysis. Issue 48 (25th November 2020) - Chen, Geng; Lin, Lv; Yan-Lin, Yang; Loretta, Chung Yuet-Foon; Han, Lin
Abstract: Background: Pressure injury (PI) is a serious problem in health care settings globally. It leads to tremendous burden both individuals and healthcare systems. Since 2008, hospital-acquired pressure injuries have been a major focus of nursing quality improvement programs within hospitals and are considered never events. However, insufficiency attention has been paid to community-acquired pressure injuries (CAPI) or pressure ulcers that occur at home or in nursing homes. The prevalence or incidence of community-acquired pressure injury has been reported but never been synthesized in a meta-analysis manner. To fill the gaps in the evidence matrix, the aims of this study are to estimate the prevalence of CAPI in the general population and to pool the overall incidence of CAPI in the general population. Methods: PubMed, Web of Science, EMBASE, CINHAL, the Cochrane Library, Chongqing VIP, and China National Knowledge Infrastructure were electronically searched to identify eligible studies updated to May 2020 to collect studies on the prevalence or incidence of community-acquired pressure injuries. Two reviewers independently will screen the literature, extracted data, and assess the risk of bias of included studies using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guideline. Meta-analyses of pooled weighted estimates will be calculated using random effect models with 95% CIs reported due to high heterogeneity. Results: Of the 5242 studies initially identified, of the 22 studies (total 479, 761 participants) 17 reporting prevalence of community-acquired pressure injury and 5 reporting incidence were included. Other results of this study will be published in a peer-reviewed journal. Conclusion: This study will summarize the pooled estimate prevalence and incidence of community-acquired pressure injuries and the pooled estimate of frequencies of different anatomic sites. Ethics and dissemination: Ethics approval and patient consent are not required, because this study is a meta-analysis based on published studies. INPLASY registration number: INPLASY202080044